Teaching language and literacy in Grade R: The value of oral storytelling. - O'Carroll, Shelley (Wordworks, 2024)
The low early grade reading levels of South African children have been well documented (Van Staden & Gustafsson, 2022), and recent PIRLS results highlight challenges with reading comprehension at Grade 4 level. Recent research indicates that these reading challenges begin long before Grade 4. Many children are not acquiring alphabet knowledge early in their reading trajectory, and these children are more likely to struggle with reading fluency and comprehension in later years (Wills, Ardington & Sebaeng, 2022). In addition, we know that reading comprehension has a strong base in oral language which develops from the earliest years of a child’s life (Dickinson & Tabors, 2001; O’Carroll & Hickman, 2012; Snow, Burns & Griffin, 1998). Although young children are too young to read, “reading comprehension has an oral language complement, and oral language can be addressed at very early ages before children can read” (Spencer, Weddle, Petersen & Adams, 2017, p. 2). Drawing on research and best practice for teaching young children, this paper highlights the key principles that underpinned the development of materials to strengthen oral language teaching in Grade R. These materials were developed as part of a story-based Home Language programme for the Gauteng Grade R Language Improvement Project, a provincial teacher training programme targeting all Grade R teachers in public ordinary schools, special needs schools and registered ECD centres in Gauteng. This materials-development project provided a unique opportunity to develop an affordable, open-source, evidence-based programme for South African children and their teachers in the 11 official South African languages. The development team needed to ensure that the teaching and assessment activities for the project were curriculum aligned and covered the content in the CAPS Home Language for Grade R.
Further information about the project as well as creative commons licensed resources can be accessed here: https://www.jet.org.za/clearinghouse/projects/grade-r-maths-and-languageimprovement-project/resources or contact the developers at info@wordworks.org.za.
Keywords: storytelling; Grade R; South Africa; early literacy; teacher development